MENINGKATKAN MOTIVASI BELAJAR DENGAN STRATEGI ARCS TENTANG MATERI PERKEMBANGAN EKONOMI-KEUANGAN DAN POLITIK PADA MASA AWAL KEMERDEKAAN SAMPAI TAHUN 1950 DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TIME GAME TURNAMEN (TGT) DI KELAS XII IPS-1 SMAN 7 BANJARMASIN - Halimatus Sa'diah (Universitas Lambung Mangkurat, 2013)
Understanding that the history lesson is rote learning resulted in a greater emphasis on verbal. Under these circumstances researchers offered the implementation of cooperative learning model type Time Game Tournament, which is a cooperative learning model in which there are elements of the game academic or weekly tournament to replace the individual test, so students do not feel bored because there is an element of the tournament. This research is a classroom action research conducted with 3 cycles. Each cycle consists of two meetings. It can be concluded: (1) The application of cooperative learning model TGT can be executed properly if the teacher can plan learning activities with good (2) Problems encountered in general can be overcome if the teacher has the willingness and ability to develop the profession (3) The application of the model TGT cooperative learning can enhance students' motivation is measured by ARCS motivational strategies that attention (attention), relevance (relevant), confidence (confidence) and satisfaction (satisfaction).Key words: History lesson, cooperative learning, Time game tournament, learning achievement